Contradições da exploração do trabalho infantil no capitalismo periférico: estudo sobre o trabalho infantil na Bahia - VASCONCELLOS, Francisca Mathilde Bittencourt (2015)
This paper aims to reflect on the contradictions involving the exploitation of child labor in peripheral capitalism, focusing on research in the social, economic and cultural conditions of child labor in the State of Bahia from a comparative study of the results of the Eradication Program Child Labor (PETI) obtained from January / 2009 to June / 2010 10 Identity Territories, comprising 47 municipalities in Bahia. Initially, it is a discussion of the current understanding of poverty in the world of work from its reproduction in peripheral capitalism and public policy undertaken as recent strategies to combat poverty in Brazil. Presents the context of child labor from the conceptual background, the advances and setbacks that favor the reproduction of poverty and social exclusion and the profile of the families involved with child labor in Bahia, to then identify the government actions to combat child labor implemented in the country and thus reveal the Peti performance conditions in Bahia, focusing on the results obtained in a survey conducted in 284 youth centers, distributed in rural and urban areas, the municipalities surveyed. The original sample reveals that the expected results from the implementation of the PETI in applied management model, are committed, especially with regard to educational activities, being performed by lay people in spaces provided by dissociated municipal managers of the school environment, it is mostly poor and inadequate for the implementation of socio-educational activities, making it impossible to carry out sports, recreational and leisure activities, making ineffective program, in that it has not been observed by public officials that Peti, in essence, should It is integrated into the basic social policies of education and health and, above all, the socio-productive inclusion policies for beneficiary families program, aiming to emancipate them socially by income and thus break the vicious circle of reproduction of poverty, a key condition to eradicate child labor, particularly its worst forms in Brazil by 2020.